Pharaoh's army - Bamford, Roger; Lodato, Doug.; Henson, Robby; Cooper, Chris, 1951-; Clarkson, Patricia; Kristofferson, Kris.; TMF (Firm); Cicada Films; Lions Gate Home Entertainment (Santa Monica, Calif. : Lions Gate Home Entertainment, 2004)
Union soldiers in search of food descend on the farm of a Confederate family and decide to stay until a soldier's wounds heal. The Union Captain falls for the woman whose husband is off at war, while her son plots revenge on the Yankees.
Title from container.
Director of photography, Doron Schlair ; music, Vince Emmett, Charles Ellis.
Chris Cooper, Patricia Clarkson, Kris Kristofferson.
MPAA rating: PG-13; for brief violence and sexual references.
DVD, region 1, Dolby Digital.
Closed-captioned.
Keywords: United States -- History -- Civil War, 1861-1865 -- Drama; Feature films; Video recordings for the hearing impaired